2015
DOI: 10.1039/c5cp01307k
|View full text |Cite
|
Sign up to set email alerts
|

Defect-dependent colossal negative thermal expansion in UiO-66(Hf) metal–organic framework

Abstract: Thermally-densified hafnium terephthalate UiO-66(Hf) is shown to exhibit the strongest isotropic negative thermal expansion (NTE) effect yet reported for a metal-organic framework (MOF). Incorporation of correlated vacancy defects within the framework affects both the extent of thermal densification and the magnitude of NTE observed in the densified product. We thus demonstrate that defect inclusion can be used to tune systematically the physical behaviour of a MOF.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
177
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 59 publications
3
177
0
Order By: Relevance
“…E in each case lies above those of other highly porous MOFs, and indeed approaches the mechanical response expected of dense hybrid frameworks 25. The large differences in elasticity with relatively small changes in SAV may allow fine‐tuning of mechanical response in these highly porous systems, though the effect of defects upon the properties of such materials remains an issue 14a, 26. The unexpected increase in resistance to pressure and the large decrease in the elastic modulus for UiO‐abdc compared to UiO‐67 are both ascribed to the presence of the azobenzene linker, which bows out of the horizontal plane.…”
mentioning
confidence: 69%
“…E in each case lies above those of other highly porous MOFs, and indeed approaches the mechanical response expected of dense hybrid frameworks 25. The large differences in elasticity with relatively small changes in SAV may allow fine‐tuning of mechanical response in these highly porous systems, though the effect of defects upon the properties of such materials remains an issue 14a, 26. The unexpected increase in resistance to pressure and the large decrease in the elastic modulus for UiO‐abdc compared to UiO‐67 are both ascribed to the presence of the azobenzene linker, which bows out of the horizontal plane.…”
mentioning
confidence: 69%
“…44,45 Recently, Goodwin and co-workers showed that correlations between defects can be introduced and controlled, yielding nanoscale defect structures. 46 The presence of these defects may alter the catalytic properties, 47,48 thermal stability, 49 proton conductivity, 50,51 and adsorption behavior 43,5255 of the host material. While recent work also indicates a decrease in bulk modulus and hence robustness upon the introduction of defects, 54,56 it remains to be investigated how the precise molecular nature of these defects alters the pressure-induced disorder in UiO-66-type materials.…”
Section: Introductionmentioning
confidence: 99%
“…Examples exist, however, such as the defect dependent NTE in UIO-66, 109 where a combination of configurational disorder together with vibrational entropy account for the material's properties. The first step towards an elaborate understanding of entropy is the analysis of each contribution and its importance within the system as a whole.…”
Section: Entropy As Design Principle?mentioning
confidence: 99%